Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland - Ingrid Wiedmann; Maria Lund Paulsen; Johnna M Holding; Mie Hylstofte Sichlau Winding; Hans Roy; Mikael K Sejr; Katja Laufer-Meiser (PANGAEA, 2025)
This dataset contains measurements of nutrients in the water column of Young Sound (NH3, Si, NOx, PO4), measurements of PON and POC in the water column (including d13C and d15N), and measurements of fluxes of POC and PON (including d13C and d15N) in short-term sediment traps. It also contains measurements in the sediment of Young Sound of oxygen penetration depth, sulfate reduction rates, Fe extraction data, dissolved Fe, dissolved Mn, sulfate in the pore water as well as the measurement of the porosity. Sediment and water was sampled in a transect along the whole Young-Sound Tyrolerfjord system. All samples were taken between 1st and 19th of August in 2019. Water samples were collected with Niskin bottles, samples for flux measurements were collected with short-time sediment traps. Sediment cores were collected with a Kajak-corer.